Klinefelter (XXY) syndrome in Sahiwal cattle: Distinguishable physical traits for early detection in field condition - SK Niranjan; Sanjay Bishnoi; Raja Ram Godara; Jayakumar S (Journal of Livestock Biodiversity, 2025)
Karyological abnormalities of sex chromosomes, most often leads to reproductive dysfunction in livestock. Almost all of the dairy cattle are invariably prone to the chromosomal aberrations in varying,but rare percentages, across the globe.Thezebucattle (Bos indicus)breeds of Indian subcontinent are seems to have fewer occurrences of such abnormalities. As chromosomal aberrations are mostly heritable, particularity if present in germ line cells, the screening of young males for such aberrations has been made mandatorybefore selecting for breeding by many of the countries, including India. A young male of Sahiwal, a well-known dairy breed of zebu cattle has been tested for chromosomal abnormalityduring pre-requisite screeningand found to possessabnormal karyotype with 61,XXY condition. The condition,first time reported in Sahiwal cattle was equivalent to Klinefelter syndrome of human being. During initial growing stage, the growth of aﬀected male calf was found to be insignificantly diﬀerent from other normal male calves; however, at later young stage, it started showing slightly feminine body conformations. In paper, we reported some important physical traits of the young male with XXY condition,which are distinguishable from the animals of normal karyotypeof same age group. Distinguishing physical traits, as conformational markers may identify syndromic young malesbefore selection in field condition;although, the condition should always be validatedthrough karyological analysis.